Pengaruh Leverage, Debt Default, Audit Tenure, Komite Audit & Opini Tahun Sebelumnya terhadap Opini Audit Going Concern : (Studi Empiris Perusahaan Sektor Consumer Cyclical yang terdaftar di BEI 2019-2023) - Rizkya Audrey Maharani; Desy Mariani (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study was conducted to analyze the effect of leverage, debt default, audit tenure, audit committe and previous year’s opinion on going concern audit opinions. The population in this study were 164 cyclical consumer sector companies listed on the indonesia stock exchange 2019 – 2023. The sample selection in this study used purposive sampling techinque, so that 100 companies were obtained as research samples. The analytical tool used in this research is logistic regression analysis. The result of this study indicate that leverage, debt default, audit tenure, audit committe have no significant effect on going concern audit opinion while the previous year’s opinion has a significant effect on going concern audit opinion.